1997
DOI: 10.3141/1570-12
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Backcalculated Moduli Using Deflections Obtained at Various Locations in a Pavement Structure

Abstract: The interpretation and use of deflection measurements on the prepared surfaces of the various pavement layers during construction are examined. Measurements were obtained from four asphalt concrete pavement test sections, two with unbound aggregate base and two with bituminous-treated base over an untreated aggregate base. Deflection basin measurements using a falling weight deflectometer were performed on the prepared surfaces of the subgrade, base layers, and asphalt concrete layers. The elastic moduli of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…), p = loading plate pressure applied by the FWD (lbf/in. 2 ), a = loading plate radius (in. ), D = depth of the pavement structure (in.…”
Section: Aashto Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), p = loading plate pressure applied by the FWD (lbf/in. 2 ), a = loading plate radius (in. ), D = depth of the pavement structure (in.…”
Section: Aashto Methodsmentioning
confidence: 99%
“…There have been reported uses of the FWD to characterize the structural properties of pavement materials. Zhou et al used an FWD to measure deflections on the prepared surfaces of various pavement materials during construction (2). That study developed mechanistic material parameters, backcalculated elastic moduli, and reported on the relationship between the moduli and the stress states associated with each material.…”
Section: Introductionmentioning
confidence: 99%
“…It is capable of evaluating HMA pavement structure containing up to five layers. The program uses an iterative approach to find a set of moduli that would provide a calculated deflection basin closest to the measured deflection basin as characterized by the root-mean-square (RMS) error (5).…”
Section: Backcalculation Of Hma Modulusmentioning
confidence: 99%
“…In the quality-control and -assurance procedure, long pavement sections are divided into homogeneous segments, and FWD tests are conducted on each layer of the segments at intervals of 10 to 20 m. Statistical tests are conducted on measured deflections in order to evaluate the construction quality as well as to identify weak points. Zhou et al additionally suggested that the coefficient of variation (COV) of the measured deflection be calculated for each homogeneous segment in order to evaluate the uniformity of construction (7).…”
Section: Deflection and Stiffness Target Valuesmentioning
confidence: 99%